2019
DOI: 10.24193/subbchem.2019.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins, carotenoids and antioxidant activity of coloured commercially available juices

Abstract: The phytochemical composition of apple, cranberry, pomegranate, carrot, and beetroot juices was determined in terms of carotenoids, anthocyanins, betalains and ascorbic acid concentration. Antioxidant potential of these beverages was also assessed using the colorimetric DPPH radical scavenging assay. The results showed that pasteurized and unpasteurized carrot and apple juices contain significant amount of β-carotene and cis-βcarotene. High total betalain content was observed in beetroot juice. Major anthocyan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…6). (Bunea et al, 2019) observed significantly higher concentrations of total carotenoids in carrot juice samples as compared to apple juices, as well. Surprisingly, no carotenoid compound was identified in commercial apple juice as compared to pasteurized and unpasteurized fresh juices.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…6). (Bunea et al, 2019) observed significantly higher concentrations of total carotenoids in carrot juice samples as compared to apple juices, as well. Surprisingly, no carotenoid compound was identified in commercial apple juice as compared to pasteurized and unpasteurized fresh juices.…”
Section: Resultsmentioning
confidence: 90%
“…Thus, this step should be monitored with caution in order to preserve the quality of products. Several authors reported that pasteurization process induces isomerization reactions of carotenoids in carrot juices and emulsion (Bunea et al, 2019;Knockaert et al, 2013). The presence of betalains was determined in three samples, which include beetroot in the mixture (No.…”
Section: Experimental Data Analysismentioning
confidence: 99%